2008
DOI: 10.1080/15376510802354201
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Induced TNF-αand TGF-β1 Expression in RAW264.7 Cells are Dependent on Src-ERK/AP-1 Pathways

Abstract: The cytokines secreted by lung macrophages have been shown to play a critical role in the pathogenesis of silicosis, tumor necrosis factor-alpha (TNF-alpha), and transforming growth factor-beta1 (TGF-beta1) are prominent cytokines in silicosis, but the underlying mechanism remains to be determined. The aim of the present study was to investigate the roles of Src-mitogen-activated protein kinase (MAPKs)/activator protein-1 (AP-1) signaling pathways in silica-induced TNF-alpha and TGF-beta1 expression in macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…In our study, the level of TNF‐α in the supernatant of SiO 2 ‐stimulated RAW264.7 cells increased with increasing time and was reduced after MT treatment. TNF‐α might induce autophagy in a Src‐ERK/AP1 pathway‐dependent manner , which is one of the three MAPK ERK families involved in cell proliferation and differentiation induced by AP1 . This result was consistent with a previous report .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the level of TNF‐α in the supernatant of SiO 2 ‐stimulated RAW264.7 cells increased with increasing time and was reduced after MT treatment. TNF‐α might induce autophagy in a Src‐ERK/AP1 pathway‐dependent manner , which is one of the three MAPK ERK families involved in cell proliferation and differentiation induced by AP1 . This result was consistent with a previous report .…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, TNF‐α is considered a central mediator of chronic inflammatory diseases. It has been reported that both TGF‐β1 and TNF‐α can be stimulated by inflammatory stimuli in macrophages 38, 39. Therefore, we next detected the production of TGF‐β1 and TNF‐α from MWCNT‐stimulated macrophages.…”
Section: Resultsmentioning
confidence: 96%
“…We observed that ROS formation in these cells was slightly lower than that in RLE-6TN cells after exposure to four of the six NMs with ROS inducing potential (Figures 2,3,4,5,6,7). The murine peritoneal macrophage cell line RAW264.7 displays similarities with alveolar macrophages [42] and has been widely used in studies investigating the pulmonary toxic potential of particulate matter [e.g. [43,44] and NMs [e.g.…”
Section: Resultsmentioning
confidence: 99%